Haemopoietic Actions of Justicia secunda Leaf Extracts in Mice - Omo Irinmwinuwa; Emeka Ifediba; Joseph Oyindamola; Onyenmechi Johnson Afonne (Faculty of Medicine Universitas Padjadjaran, 2022)
Objective: To evaluate the haemopoietic effects of Justicia secunda leaf ethanol, n-hexane, ethyl acetate, and n-butanol extracts in mice and compare these effects with the effects of standard antianaemic agents.Methods: Sixteen groups of mice, six in each group, were used for the study. Anemia was induced in Groups 1 to 12 using 20 mg/kg i.p. phenylhydrazine (PHZ) daily for 2 days, followed by either ethanol, n-hexane, ethyl acetate or n-butanol extracts for 6 days. Groups 13 and 14 were induced for anemia and then received 200 mg/kg ferrous sulphate and vitamin B12 for 6 days. Group 15 (positive control) received 20 mg/kg PHZ i.p. only, while group 16 (negative control) was untreated. Blood was collected from the retro-orbital plexuses of the mice into EDTA-containing bottles on the 7th day and analyzed for hemoglobin (Hb) level, packed cell volume, mean cell hemoglobin concentration, and mean cell volume. Red blood cell, white blood cell, and platelet counts were also measured.Results: The ethanol leaf extract of J. secunda significantly increased the hematological parameters of mice compared to the positive and negative controls (p < 0.05). However, the n-hexane, ethyl acetate, and n- butanol extracts showed greater hemopoietic effects (p < 0.001) than the ethanol extract and standard antianemic drugs. The extract of J. secunda leaf tended to stimulate erythropoiesis comparable to the standard antianemic drugs, especially the n-hexane.Conclusion: Justicia secunda leaf extracts exert hemopoietic actions in mice, while the n-hexane extract shows greater haemopoietic activities than ferrous sulphate and vitamin B12.